Design of optimal velocity tracking controllers for one and two-body point absorber wave energy converters. (December 2020) - Stock, Adam; Gonzalez, Carlos
Abstract: Point absorber Wave Energy Converters (WECs) are typically operated using linear damping control in which the resistive force of the power take-off (PTO) is linearly proportional to the velocity of the floater. Such algorithms are used predominantly due to their simplicity and ease of application, however, it is known that such control is far from optimal in terms of energy capture. Previous studies in the literature have seen a number of different, more advanced control methodologies proposed, however, in the main, these have been applied to single body point absorbers. The main objective of the work presented here is to develop and implement a novel two-body WEC optimal velocity tracking controller design methodology. First, an Optimal Velocity Tracking (OVT) controller is designed using a novel controller design model and applied to a WEC-Sim model of a utility scale single-body point absorber. The methodology is then extended to the two-body point absorber WEC case and an OVT controller is designed for a utility scale two-body WEC. The increase in energy capture for a site in UK waters, based on WEC-Sim simulations and compared to typical linear damping control, is 23% for the one-body WEC and 20% for the two-body WEC. Highlights: First time Optimal Velocity Tracking control applied to a 2 body WEC in simulations. Cummins' equation formulated for two body devices and used to generate control models. Quicker and easier controller design: simple and effective controllers produced. Proposed strategy shows improved energy capture of 20% compared to linear damping. Improvements likely to be even greater for more narrow-banded WEC designs.